Effect of Foliar Application of Micronutrients on Growth and Yield of Rice (Oryza sativa L.) and Soil Quality under SRI system - Pal, Muneesh; Verma, Archana; Singh, Avdhesh Pratap; Sirazuddin (International Journal of Economic Plants, 2026)
A field experiment was conducted during the kharif season (June–August) of 2023 to assess the effect of solo and combined foliar application of micronutrients on growth, yield, and soil nutrient status of rice (Oryza sativa L.). Eight treatments i.e., T1: Control RDF, T2: RDF+Foliar application of Zinc 0.5% at 30 DAT, T3: RDF+Foliar application of Zinc 0.5% at 60 DAT, T4: RDF+Foliar application of Iron 1.0% at 30 DAT, T5: RDF+Foliar application of Iron 1.0% at 60 DAT), T6: RDF+Foliar application of Zinc 0.5% and Iron 1.0% at 30 DAT, T7: RDF+Foliar application of Zinc 0.5% and Iron 1.0% at 60 DAT, T8: RDF+Foliar application of Zinc 0.5% and Iron 1.0% at 30 and 60 DAT, were taken in RBD with three replications. Results indicated that combined foliar application of zinc and iron significantly improved growth, yield, and soil nutrient status of rice compared to the control and individual applications. Treatment T₈ recorded the highest grain yield (590 kg ha-1), straw yield (89.3 q ha-1), and biological yield (147.3 q ha-1). Soil available nitrogen, phosphorus, potassium, zinc, and iron were also significantly higher under T₈. The study concludes that foliar application of Zn and Fe at critical growth stages, along with soil application of RDF, was an effective strategy for enhancing rice productivity and improving soil fertility.